Ask the children: reframing extended education offerings quality and policy through children’s perspectives - Näpfli, Jasmin; Schweinberger, Kirsten (Frontiers in Education, 2025)
Although the UN Convention on the Rights of the Child mandates that children’s voices must be heard in matters affecting them, their perspectives on the quality of Extended Education Offerings (EEOs) are rarely considered. This study explores how children perceive their participation opportunities in EEOs. Conducted in a Swiss canton where EEOs are well-established within a quality framework, the study involved 46 photo tours followed by group discussions with 194 children aged 5–12 across nine EEOs. These data were analyzed using qualitative content analysis focused on aspects of participation. The results reveal differences in participation practices, ranging from formalized meetings with guidelines to settings with limited or informal opportunities. Many children expressed a sense of self-determination, particularly in free play, and emphasized the importance of receiving feedback in participation processes. The analysis identified recurring patterns across participation dimensions, showing that self-determination and meaningful feedback foster children’s sense of agency, while lack of transparency leads to frustration and perceived tokenism. These findings emphasize the need for intentional, context-sensitive strategies to embed participation more consistently within EEO practices. Given the significant role that EEOs play in children’s lives, it is crucial to translate these insights into practice. In a short brief example, we illustrate how the findings informed the revision of the cantonal quality framework. While children are not consistently able to participate directly in policymaking, this example underscores the critical role of researchers as knowledge brokers who can represent children’s perspectives. By fostering an “interactive space” between research, practice, and policy, researchers can ensure that children’s voices inform quality development in EEOs. Even when children are not directly involved, their perspectives — conveyed through research — can shape institutional frameworks and strengthen participatory principles in educational contexts.